Dampak Penggunaan Sosial Media Terhadap Kinerja Bisnis - Friska Mastarida (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The purpose of this paper is to review the literature on the use of social media on business performance. This study uses a qualitative research design through library research techniques. The author presents various journal publications in the field of marketing and management from 2010 to 2020 using a systematic literature review approach. Highlight that four dimensions that encourage the development of exploitation and exploration of social media that are firm-spesific companies to business performance are the relational dimension, cognitive dimension, structural dimension and knowledge transfer dimension. This area of ​​research requires a great deal of attention both theoretically and empirically, to analyze and develop new categories of antecedents of social media adoption on business performance. Further studies emphasize sustainable innovation. This paper provides a complete framework regarding social media adoption on business performance